Analysis of forward contracting by California dairy producers on input and output sides using least- cost and profit-maximization methods - Karlin, Joel (Kansas State University, 2010)
Economically optimized ration formulations were used to test whether California dairy producers who implemented price risk management strategies on both the input and output sides achieved significantly higher net returns as measured by milk income minus feed costs compared to producers who bought feed and sold milk on the spot market. Two ration formulation models were developed, a least cost and a profit-maximization. The least cost method formulates a ration that meets the nutritional requirements of a lactating cow at the lowest possible cost for a given level of milk production. The profit maximization model incorporates into its algorithm a production function between net energy intake and milk production that increases at a decreasing rate. For today's high producing cows, after being supplied with enough energy to meet maintenance requirements, all additional energy is partitioned for milk production. Up to a certain point, depending on the price of milk and the price of feed, the cost of providing additional feed units is more than offset by the revenues derived by the extra milk produced from the larger quantities of feed consumed. The profit-maximization model used formulates a ration using both feed and milk prices where the cost of the last unit of feed provided is equal to the revenues of the last unit of milk produced. To compare returns, a ration program was designed that could either use spot or forward values for feed costs and milk price to economically optimize the ration on a weekly basis in the cow’s milk production cycle. To better gauge the impact of price volatility on both the input and output sides and to account for the extended nature of the forward contracts, the 305-day lactation cycle of a high producing cow over six successive cycles was used. The federal order Class III milk price was used for milk values and it was assumed that unless the producer engaged in some sort of forward contract, the milk price received was the monthly Class III value. To account for forward sales, the Class III futures contract traded at the Chicago Mercantile Exchange was used. For the feed prices, the ration model had a library of 16 different ingredients, 11 of which had forward and spot values. Similar to the output side, it was assumed that unless the producer engaged in some sort of forward contract the feed price used was the spot value averaged for each month. Most California dairy operators use some version of the least-cost method when formulating their rations. A large number also forward contract a significant portion of their feed as the concept of forward contracting feed is much more common in the western U.S. as compared to other regions in the country. Conversely, there has been little interest in locking in future milk prices as the tools for forward contracting are relatively new and many producers are not familiar with the mechanics. This helps explain the limited use of the profit-maximization model since milk prices are an integral part of this process. Results of this study show that producers who formulate using the profit-maximization model attain higher milk production and derive higher milk revenues, albeit with higher feed costs. Nonetheless, across every situation, that is whether one forward contracts feed, milk, or some combination thereof the profit-maximization model returned anywhere from $0.14 to $0.19 of milk revenues in excess of feed costs per hundredweight of milk as opposed to the least-cost method. For a producer milking 1,000 cows this represents another $50,000 to $70,000 of income per year. The results also show that whether least-cost or the profit-maximization method is employed, feed costs were lower when producers forward contract at least a portion of their needs. Milk prices, on the other hand, were lower relying on the spot market as opposed to either of the two forward milk contracting models that were developed. Finally, the variability of returns as measured by the coefficient of variability show less volatility in revenues when producers forward contract milk and less variability with input costs when producers forward contract feed.
Keywords: Milk Production; Risk Management; Optimization; Ration Formulations; Economics, Agricultural (0503)